Hollow pursuits - Matthew Leggatt (Eludamos)
In so many ways the vision of the future imagined in the Star Trek universe seems painfully distant. Perhaps, the closest the show has come to anticipating the world as it is today, however, can be found in its depiction of the holodeck as the crew’s primary space for leisure. This article focuses on episode 21, season 3 of Star Trek: The Next Generation, ‘Hollow Pursuits’, in which we meet Reginald Barclay, a nervous engineer who becomes addicted to the ship’s virtual reality simulator. Taking its cue from Janet Murray’s book, Hamlet on the Holodeck, writing on the Enterprise’s leisure technology has tended to explore the holodeck’s role as a theatrical story-telling device. However, in ‘Hollow Pursuits’, I argue, Barclay’s use of the software resonates far more with its closest comparator today: virtual reality videogaming. For Barclay the holodeck blurs the line between the virtual world and reality in ways that make other crew members uncomfortable. In doing so, as this paper demonstrates, it also reveals flaws in The Next Generation’s utopia particularly in relation to desire, addiction, therapy, and ‘play’.